9. Digital Technologies - The Future Way of Learning in Higher Education - Aliu Nora; Aliu Vlora; Gashi Modest (Sciendo, 2023)
Digitalization trends have moved forward with accelerated steps, surrounding all spheres of our lives with the provision of light services, faster and less expensive communications, more functions, and a great influence on increasing quality of life. In developed countries, digitization of education is seen as one of the priority goals for achieving sustainable development. Higher education is an essential pillar in developing new knowledge economies for the twenty-first century, and Kosovo national authorities are strategically oriented toward the digitalization of higher education. Digitization includes a wide range of activities ranging from lecturers, group work lectures, and inclusion in individual or group study, and exams as an integral part of the revolutionization of higher education. The period of COVID19 has pushed forward the digitization of education in many countries of the world. In Kosovo, this was the period that established the dividing boundaries between the traditional multi-century teaching eras with the new digital era. This period is also characterized by the challenges faced by teaching and learning in the use of efficient digitized methods. This paper explores the impact of digitization on teaching and learning, specifically in medicine and architecture. Also, this work is intended to offer a model of how digital transformation can be used to build competitive advantages for universities. Based on the condition of the accreditation agency and the standards of the International Society for Technology in Education, we can say that the use of software and artistic methods in teaching processes affects the development and advancement of young people.